Repair of thalassemic human β-globin mRNA in mammalian cells by antisense oligonucleotides - Sierakowska, Halina (The National Academy of Sciences of the USA, 1996)
In one form of β-thalassemia, a genetic blood disorder, a mutation in intron 2 of the β-globin gene (IVS2-654) causes aberrant splicing of β-globin pre-mRNA and, consequently, β-globin deficiency. Treatment of mammalian cells stably expressing the IVS2-654 human β-globin gene with antisense oligonucleotides targeted at the aberrant splice sites restored correct splicing in a dose-dependent fashion, generating correct human β-globin mRNA and polypeptide. Both products persisted for up to 72 hr posttreatment. The oligonucleotides modified splicing by a true antisense mechanism without overt unspecific effects on cell growth and splicing of other pre-mRNAs. This novel approach in which antisense oligonucleotides are used to restore rather than to down-regulate the activity of the target gene is applicable to other splicing mutants and is of potential clinical interest.